Analysis of the Frequency of Consumer Visits to Pizza Hut Fast Food Restaurants in Banda Aceh City - Fahmi, Ijal (Indonesian Journal Economic Review (IJER), 2024)
This research aims to determine whether product, price, promotion, location and lifestyle variables influence the frequency of consumer visits to the Pizza Hut fast food restaurant in Banda Aceh and which variables are the most dominant in influencing the frequency of consumer visits. The research respondents were 80 consumers taken using convenience sampling. Data collection was carried out by distributing questionnaires to each respondent. Furthermore, the data analysis equipment used is multiple linear regression. The research results show that product, price, promotion, location and lifestyle factors have a positive influence on the frequency of visits by consumers of Pizza Hut fast food restaurants in Banda Aceh. The factor that has the greatest influence on the frequency of consumer visits is the product factor. The relationship between product, price, promotion, location and lifestyle factors and the frequency of visits is not close. Statistical testing shows that simultaneously the five factors (product, price, promotion, location and lifestyle) have a significant effect on the frequency of visits by consumers of Pizza Hut fast food in Banda Aceh. Meanwhile, partially only product factors have a significant influence. On the other hand, price, promotion, location and lifestyle factors do not partially have a significant effect. The conclusion that can be drawn from this research is that the frequency of consumer visits to the fast food restaurant Pizza Hut Banda Aceh is influenced by product, price, promotion, location and lifestyle factors. However, the factor that has the most dominant influence on visit frequency is only the product factor.